Rural industry in China : performance and potential -a study of township, village and private enterprises in Jiangsu Province. - Li, Wen Zhi. (2011)
The rapid growth of township, village and private enterprises (TVPEs) in China is a special phenomenon. The objective of this research is to investigate the productivity of input factors to determine the driving forces behind the rapid growth and to analyze the potential for the further development of rural industry. In this research study, I analyze the productivity of different categories of labor and capital by estimating production functions using the micro data of 140 firms located in 15 counties in Jiangsu province for the years 1989 and 1990. Production is measured by net output in 1990 price; regressors include different categories of labor and capital. The GLS method is employed to overcome the tested heteroskedastic problem. The potential for the further development of the rural industry is assessment by evaluating input constraints and government policies. It is found that capital has played a more important role than labor. The big driving force for the TVPE rapid growth is due to the fact that the marginal capital productivity is much higher than the loan rate of state banks. However, the fact that the marginal labor productivity is close to labor's remuneration implies that the growth of TVPEs can be enhanced by increasing capital input and not labor input. It is also found that highly educated employees are much more productive than those without tertiary education. Work experience is found in this study to be a less important factor for the development of rural enterprises in China.